Hacking Darwin : genetic engineering and the future of humanity - Metzl, Jamie Frederic (Sourcebooks, Inc., 2019)
"Genetic engineering isn't some far-off fantasy. It's arriving faster than most of us understand or are prepared for. When we can engineer our future children, massively extend our lifespans, build life from scratch, and recreate the plant and animal world, should we? At the dawn of the genetics revolution, our DNA is becoming as readable, writable, and hackable as our information technology. But as humanity starts retooling our own genetic code, the choices we make today will be the difference between realizing breathtaking advances in human well-being and descending into a dangerous and potentially deadly genetic arms race. From a leading geopolitical expert and technology futurist comes a groundbreaking exploration of the many ways genetic engineering is shaking the core foundations of our lives--sex, war, love, and death. Enter the laboratories where scientists are turning science fiction into reality. Look toward a future where our deepest beliefs, morals, religions, and politics are challenged like never before and the very essence of what it means to be human is at play. More than ever, it's critical for everyone to learn how our species will function and re-create itself in the new world. Passionate, provocative, and highly illuminating, [this book] is a guide to a future that has already begun."--Dust jacket.